2022
DOI: 10.1155/2022/5339809
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation, the Physicochemical Assessment, and the Antimicrobial Action of Nanocurcumin‐Loaded Dental Temporary Restorative Material

Abstract: Introduction. The aim of this study was to prepare a temporary restorative material containing curcumin nanocrystals and to evaluate the physicochemical properties and the antimicrobial action against Enterococcus faecalis (E. faecalis), Staphylococcus aureus (S. aureus), and Escherichia coli (E. coli). Materials and Methods. Dental temporary restorative material was physically mixed with curcumin nanocrystals at weight percentages of 80/20 and 70/30. The prepared materials were then subjected to the physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The pattern of rapid release of curcumin in the outer surface of the composites and continuous release in the sixth to 35th days related to the nanoparticles are more internal and may have electrostatic interactions with the gelatin matrix and their release takes time [29]. Other investigators have also reported similar release patterns for curcuminloaded dental materials [30,31]. Indeed, to achieve a slow-release behavior, either the sustained-release polymers are needed or a suitable cross-linker is used [32].…”
Section: Discussionmentioning
confidence: 93%
“…The pattern of rapid release of curcumin in the outer surface of the composites and continuous release in the sixth to 35th days related to the nanoparticles are more internal and may have electrostatic interactions with the gelatin matrix and their release takes time [29]. Other investigators have also reported similar release patterns for curcuminloaded dental materials [30,31]. Indeed, to achieve a slow-release behavior, either the sustained-release polymers are needed or a suitable cross-linker is used [32].…”
Section: Discussionmentioning
confidence: 93%